Impact of ethical leadership on organizational cronyism through mediating role of ethical culture and moderating role of leader member exchange - Adnan Riaz; Shams u Zaman (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2018)
The purpose of this study is to develop a mediation model for understanding how ethical leadership influences organizational cronyism via ethical culture. This study further investigates the role of leader-member exchange in moderating the effects of ethical culture on organizational cronyism. In contrast to previous research, which has examined the direct effects of ethical leadership on ethical culture, our study examined the underlying mediated and moderated mechanism. A representative sample of 306 employees was collected from organizations operating in private sector. Inferential statistics was applied with the help of descriptive, correlation, moderated and mediated regression analysis. Results confirmed all the direct hypothesis as well as the mediating role of ethical culture was substantiated between ethical leadership and organizational cronyism. LMX also moderated the inverse relationship between ethical culture and organizational cronyism such that the relationship was stronger for employees enjoying high leader member exchange relationship. Discussion and implications are presented based on the results of the study.
Keywords: 330; ethical leadership; ethical culture; organizational cronyism; leader member exchange; private sector; Pakistan